Situation of Offenses Observed in Maritime Fishing and Proposal for Measures to Improve the Surveillance System: Case of the National Fisheries Surveillance and Police Center (CNSP) in Guinea (International Journal of Scientific Research in Science and Technology, 2024)
Research work on the theme “Situation of offenses observed in maritime fishing and proposal for measures to improve the surveillance system: case of the National Fisheries Surveillance and Police Center (CNSP) in Guinea » Conakry took place in the period from September 14 to December 14, 2022 inclusive. The objective of this work was to take stock of the offenses recorded in fishing with a view to proposing solutions for improving the surveillance system. To achieve this objective, the following methodology was adopted: consultation of executives and exploitation of archives; survey of surveillance agents; identification and descriptions of the surveillance system; identification of the offenses and fleet involved in the Guinean EEZ in recent years; determination and classification of the causes of offenses; evaluation of the surveillance system; proposal for improved measures of the surveillance system. Monitoring of this approach revealed that: the offenses committed in the Guinean EEZ are related to the fishing gear used; administrative documents and fishing operation zones. According to records, for the period from 2006 to 2021, there were 308 boardings. The rate of infringements in IP is 59%, 25% in PAM and 16% in PSI. The flags which have committed more IP infringements are Chinese 86 and Korean 60; in PSI the Chinese 17 and the Senegalese 16 and in PAM the Guineans 33, Senegalese 23 and the Leonese 18. The stakeholder survey revealed that the number of vessels monitored by VMS in 2021 was 79 in PI and 49 in PSI. The main documents inspected at sea are generally: registration certificates, crew, rescue equipment, gross tonnage, coastal state fishing authorization, maritime radio license. The fleets involved in the infringements in the Guinean EEZ from 2006 to 2022 numbered 135 including 80 demersal trawlers, 7 cephalopod boats, 21 shrimp boats, 22 pelagic trawlers and 5 cargo ships. The improvement of the surveillance system in Guinea may be more efficient, incombining the AIS and VMS system in fisheries surveillance, by creating a marking system for fishing gear, by purchasing very powerful launches and maintaining the confidentiality of patrol operations.